Os reservatórios eutrofizados da região tropical semiárida atuam como emissores ou como sequestradores de dióxido de carbono? - Mendonça Júnior, Jurandir Rodrigues de (2014)
The aquatic ecosystems can play a role as carbon-dioxide-source or carbon-dioxide-sink systems due to the high predominance of heterotrophic or autotrophic metabolism. The primary production can strongly affect the carbon balance (CO2) through the consumption of carbon dioxide in the photosynthesis, especially in eutrophic environment, acting as a carbon sink. The present study tested the hypothesis that the eutrophic reservoirs in tropical semi-arid region are carbon dioxide-sink systems due to the high primary productivity presented in these systems. Five Brazilian reservoirs from the semi-arid in the northeast region were monitored monthly during four years (2010 to 2013) with a prolonged drought event identified during the study. The results showed an increasing level of eutrophication over the period of prolonged drought, with the predominance of autotrophy. Significant negative correlations were observed between the partial pressure of CO2 (pCO2) (p<0,001) and chlorophyll-a in the Boqueirão, Passagem das Traíras, Dourado and Gargalheiras reservoirs, showing a pattern of the carbon dioxide-sink systems. However, this pattern was not found in Cruzeta reservoir. In summary, in the tropical semi-arid region, hydrological and morphometric variables can lead to different behaviors of the water-supply reservoirs on the carbon metabolism. The eutrophic reservoirs evaluated showed a negative relationship between pCO2 and Chl-a, which suggests that these water bodies show an autotrophic metabolism and behave as carbon dioxide- sink systems